Layanan Konseling Kelompok Dengan Teknik Latihan Asertif Untuk Meningkatkan Asertivitas Siswa Kelas VIII SMP YPS SINGKOLE - Asriani Asriani; Muhammad Anas; Putra Jaya (Universitas Negeri Makassar, 2021)
The aim of this research is to enhance the assertiveness of grade 8 students of SMP YPS Singkole (YPS Singkole Junior High School) through applying a group counselling service and assertive technique exercise. The research which is run two cycles also uses quantitative research as a method which designed in guidance action research. The subjects of the research are the students with low assertiveness level. In collecting data, the writer uses questionnaire, observation, and interview. The data is then analyzed through an evaluation questionnaire to see the success of the research or the percentage of the reinforcement should have been given to the subjects. The result shows that the assertive technique exercise applied in both cycles has improved the subjects’ assertiveness level, from low to medium and high.